Ethical Issues in the Iran\'s Sport Media: Perceptions ‎of National Team Coaches - Amin Rayat; Mehdi Rayat; Leila Rayat (The Society of Aging and Physical Activity (SAPA), 2017)
This article is "Retracted" at 2018/04/04 due to "Plagiarism" totally from "Çimen, Z. Ethical Issues in Turkish Sport Media: Perceptions of Professional Football Players. South African Journal for Research in Sport, Physical Education and Recreation. 2012; 34 (1)."